Impact of Religion on Sustainable Development in Nigeria - Olusegunajakaye Abraham; Zubair Riskat Abiola; Oladele Taiwo Omolara; Jubril AbdulAzeez (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2024)
Sustainable development has always been the dream of all levels of society and communities. There is no society or community anywhere in the world that does not aspire and hope for sustainable and lasting development. Therefore, Nigeria as a country has for many years yearned and hoped for sustainable development. This desire for development cuts across the social strata of Nigerian society from food strata, roads, and rural infrastructure to socioeconomic and even political strata. This paper is of the view that religion can be a very powerful tool for achieving sustainable development in Nigeria. This is believed to be the developmental role of religion in any society. If religion (its principles, belief systems, and practices) are applied positively to development in Nigeria, then sustainable development will be realized in Nigeria. This research aims to identify how religious values and teachings can encourage or hinder environmental conservation efforts, social welfare, and sustainable economic growth. The subjects in this research were members of community groups. The research method used is descriptive qualitative. This research implies that religion has great potential to encourage sustainable practices, which means that governments and other stakeholders need to involve religious organizations in development initiatives more actively.